2023
DOI: 10.25082/amler.2023.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Creating a watermill through steam activities for preschool children in the school yard

Abstract: STEAM (Science, Technology, Engineering, Arts and Mathematics) initiatives engage in classroom and schoolyard activities in early childhood education. In early childhood, learning through play provides children with the resources they need for an enjoyable learning environment, especially when the activities take place in the schoolyard, as this is where children can better concentrate and, at the same time, increase their creativity. This work investigates whether preschool children can create watermills thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, a lack of study has been conducted that focuses on establishing an interactive digital flipbook for specific students, such as those who learn at a relatively slow rate (slow learners). In addition, the concept of designing a flip book still needs to be added to the models offered, such as those based on gamification (Skaraki, 2023). To fill those gaps, in this research, we focused on developing an interactive gamification-flip-book for slow learners assuming that flipbook is a solution as a digital media offered in which it is a challenging endeavour to instruct students classified into slow learners.…”
Section: Introductionmentioning
confidence: 99%
“…However, a lack of study has been conducted that focuses on establishing an interactive digital flipbook for specific students, such as those who learn at a relatively slow rate (slow learners). In addition, the concept of designing a flip book still needs to be added to the models offered, such as those based on gamification (Skaraki, 2023). To fill those gaps, in this research, we focused on developing an interactive gamification-flip-book for slow learners assuming that flipbook is a solution as a digital media offered in which it is a challenging endeavour to instruct students classified into slow learners.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers reported that students' distraction and limitation of understanding were slightly affected. Finally, exposing students to technological media that are not based on educational content and viewing inappropriate content leads to poor physical, social and cognitive development Korb, 2019;Surirman et al, 2019;Skaraki, 2023;Skaraki & Kolokotronis, 2022).…”
Section: Discussionmentioning
confidence: 99%